Practical relevance of the new regulation regarding unfair practices in business-to-business relationships in the agri-food chain: Directive (EU) 2019/633 - Vázquez Ruano, Trinidad; Latorre Ruiz, Juan (Przegląd Prawa Rolnego, 2019)
The work we present addresses the new challenges that arise in the European framework regarding the agri-food chain, following the recent approval of Directive (EU) 2019/633 of 17 April on unfair trading practices in business-to-business relationships in the agricultural and food supply chain. The European Commission has dealt with small and medium-sized food and agricultural companies, producers and farmers in the food supply chain who represent a vulnerable sector in the agri-food supply chain. The new normative text aims to limit the possible unfair trading practices that are carried out in the supply chain and that involve the alteration of the equal opportunities of small and medium-sized food and agricultural companies, producers and farmers. Fundamentally due to the diverse negotiation capacity, in accordance with the proposals for the modernisation of the Common Agricultural Policy (CAP).